3D deep learning with Python : design and develop your computer vision model with 3D data using PyTorch3D and more /: design and develop your computer vision model with 3D data using PyTorch3D and more. (2022) - Ma, Xudong; Hegde, Vishakh; Yolyan, Lilit
No abstract available